Financial development, economic growth, international trade, and environmental degradation the ASEAN+ case - Quejada, Angel Derrickvhel (School of Economics, University of the Philippines Diliman, 2019)
Carbon emission is the leading source of Greenhouse Gases in the world which causes global warming. Its serious effects like decreased crop production, sinking islands due to rising sea levels, and prevalence of water_borne diseases due to frequent flooding are widely felt by ASEAN Plus countries where most of the fastest emerging economies are. As such, this research aims to find causal association between economic growth, CO2 emissions, financial development, and trade openness using simultaneous_equation panel data models for a panel of 10 ASEAN Plus countries over the period 1990_2017. Following a generalized method of moments (GMM) technique, I have found out that a bidirectional causality exists between economic growth and CO2 emissions. Feedback hypothesis is validated between financial development and CO2 emissions. Trade openness and CO2 emissions are interrelated i.e. bidirectional causality. The findings show a bidirectional causality between financial development and economic growth. Feedback hypothesis is identified between trade openness and economic growth. My empirical results also verified the existence of Environmental Kuznets Curve (EKC). Empirical findings of the study substantiate that the policymakers of the ASEAN Plus nations must adopt green energy initiatives either through local research and development or technology transfers through trade and Foreign Direct Investments (FDI). Financial development targetted towards green innovation and environment_friendly ventures are highly encouraged to abate its effect on carbon emissions. Furthermore, the effect of urbanization and capital formation to carbon intensity can be mitigated by material use efficiency and agglomeration. These empirical insights will help ASEAN Plus sustain economic development and improve the environmental quality.